2023
DOI: 10.1111/jmp.12661
|View full text |Cite
|
Sign up to set email alerts
|

A pharmacokinetic study of extended‐release buprenorphine in cynomolgus monkeys (Macaca fasicularis)

Abstract: BackgroundA novel buprenorphine (BUP) extended‐release formulation (BUP‐XR) produced as a lipid‐encapsulated, low viscosity BUP suspension for subcutaneous (SC) injection to control pain was evaluated for pharmacokinetics and safety in four adult male cynomolgus monkeys.MethodsEach animal was given 0.2 mg/kg reformulated BUP‐XR SC. Clinical observations were made during the course of the study. Blood samples were obtained from each animal before BUP‐XR administration, 6, 24, 48, 72, and 96 h post‐BUP‐XR inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…In the cynomolgus macaque ( Macaca fascicularis ) and the common marmoset ( Callithrix jacchus ), therapeutic buprenorphine plasma levels lasted as long as 96 h after XRB administration. 11,25 Evaluation of another non-FDA approved long-lasting buprenorphine, SRB, in diabetic Yucatan miniature swine revealed therapeutic plasma levels that surpassed 96 h. 17 Furthermore, our study revealed XRB (Ethiqa) injection sites sustained minimal changes including granulomatous inflammation and cholesterol clefts – consistent with what has been reported with injection of XRB (Ethiqa) in other species and likely due to the lipid-bound in a medium chain fatty acid triglyceride (MCT) oil. 11,16,22,23,25 Therefore, XRB (Ethiqa) extra-label use in swine increases our options for long-lasting and safe analgesia in swine.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In the cynomolgus macaque ( Macaca fascicularis ) and the common marmoset ( Callithrix jacchus ), therapeutic buprenorphine plasma levels lasted as long as 96 h after XRB administration. 11,25 Evaluation of another non-FDA approved long-lasting buprenorphine, SRB, in diabetic Yucatan miniature swine revealed therapeutic plasma levels that surpassed 96 h. 17 Furthermore, our study revealed XRB (Ethiqa) injection sites sustained minimal changes including granulomatous inflammation and cholesterol clefts – consistent with what has been reported with injection of XRB (Ethiqa) in other species and likely due to the lipid-bound in a medium chain fatty acid triglyceride (MCT) oil. 11,16,22,23,25 Therefore, XRB (Ethiqa) extra-label use in swine increases our options for long-lasting and safe analgesia in swine.…”
Section: Discussionsupporting
confidence: 79%
“…56 Studies comparing local injection reactions of SRB and XRB (Ethiqa) in multiple species revealed XRB (Ethiqa) had less inflammatory changes. 11,23,25 These findings encourage further optimization of long-lasting buprenorphine formulation for swine and support the extra-label use of the FDA-indexed XRB (Ethiqa) in this species.…”
Section: Discussionmentioning
confidence: 58%